2021
DOI: 10.1071/sh20220
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of accessing a medical termination of pregnancy through a Queensland regional sexual health service: a qualitative study

Abstract: Background An estimated 25% of Australian women will undergo induced abortion. Few studies have explored Australian women’s experiences of accessing medical termination of pregnancy (MToP). This study explored the experiences of women accessing MToP through a regional sexual health service in North Queensland. It aimed to determine the aspects of the process from seeking information about abortion to completion that worked well and to identify areas for improvement. Methods. Semi-structured telephone interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Other studies in rural Australia have focused on women's experiences of abortion services once reached and the perspective of service providers about the delivery of care, including provision via telehealth (Doran and Hornibrook 2016;Dawson et al 2017;Hulme-Chambers et al 2018;Fix et al 2020;Ireland et al 2020;Cashman et al 2021;Mazza et al 2021;Malatzky and Hulme 2022). These studies have also found results similar to ours, that multiple systemic challenges exist for rural women when accessing services.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Other studies in rural Australia have focused on women's experiences of abortion services once reached and the perspective of service providers about the delivery of care, including provision via telehealth (Doran and Hornibrook 2016;Dawson et al 2017;Hulme-Chambers et al 2018;Fix et al 2020;Ireland et al 2020;Cashman et al 2021;Mazza et al 2021;Malatzky and Hulme 2022). These studies have also found results similar to ours, that multiple systemic challenges exist for rural women when accessing services.…”
Section: Discussionsupporting
confidence: 79%
“…In a study examining access, equity and costs of induced abortion in Australia, the strongest predictor of late presentation (beyond 9 weeks) was living ≥4 h from the abortion clinic (Shankar et al 2017). Access barriers are well documented in relation to abortion care in Australia (Dawson et al 2017;Hulme-Chambers et al 2018;Fix et al 2020;Ireland et al 2020;Cashman et al 2021;Mazza et al 2021); however, little is known about the role of local generalist primary care providers in rural settings as the first point of contact for women seeking advice or services for unintended pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…These clinical scenarios were rare in our study, and usually arose at extremely pre‐term gestation ages when management, particularly regarding the advisability of feticide, was tailored to the individual. Finally, we could not investigate barriers to late termination of pregnancy service, such as financial, family, community, and social opposition, as well as domestic violence and mental health problems 17‐19 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, we could not investigate barriers to late termination of pregnancy service, such as financial, family, community, and social opposition, as well as domestic violence and mental health problems. [17][18][19]…”
Section: Limitationsmentioning
confidence: 99%
“…58 The COVID-19 pandemic facilitated the creation of MBS items for telehealth, which has made these services more accessible across Australia. 59 However, many women remain unaware of the availability of telehealth as a mode of delivery for reproductive health services, 60 61 highlighting the importance of raising awareness of this option among both women and practitioners.…”
Section: The Opportunities: Strategies For Increasing Access To Contr...mentioning
confidence: 99%